Cement clinker based on copper tailing sand, preparation method and application
By replacing copper tailings sand with siliceous raw materials in traditional cement clinker and combining with high-temperature calcination technology, the problems of resource depletion and high energy consumption in traditional cement clinker production are solved, and efficient recycling of copper tailings sand and improving the performance of cement clinker are achieved.
Patent Information
- Application Number
- CN202411714429.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-04-11
AI Technical Summary
Traditional cement clinker production has problems of resource depletion and high energy consumption, and insufficient recycling and utilization of copper tailings sand.
By replacing copper tailings sand with siliceous raw materials in cement clinker, cement clinker composed of copper tailings sand, clay and limestone was prepared, and processed using a high-temperature calcination process.
The efficient recycling and utilization of copper tailings sand has been achieved, the raw material cost of cement clinker has been reduced, and the performance of cement clinker has been improved. The free calcium oxide content does not exceed 1%, and the hydration compressive strength of 28 days reaches more than 32MPa.
Smart Images

Figure BDA0005156581580000091 
Figure BDA0005156581580000101 
Figure BDA0005156581580000121
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of copper tailings sand recycling and utilization, and in particular to cement clinker based on copper tailings sand, a preparation method and application thereof. Background Art
[0002] Copper tailings are waste discharged after copper ore is crushed, ground and flotated. They contain high levels of chemical components such as SiO2, CaO, Fe2O3, Al2O3 and MgO, which are similar to the composition of raw materials for building materials such as cement, glass and ceramics.
[0003] Traditional cement clinker production often uses raw materials such as limestone and clay, which have problems such as resource depletion and high energy consumption. If copper tailings sand can be used as siliceous raw materials, it can not only alleviate the tailings accumulation problem, but also reduce production costs and improve economic benefits. Summary of the invention
[0004] In order to solve at least one of the above technical problems, a method is developed to replace the siliceous raw materials in cement clinker with copper tailings. The present application provides cement clinker based on copper tailings, a preparation method and application.
[0005] On the one hand, the present application provides a cement clinker based on copper tailings sand, wherein the cement clinker is prepared by including the following components in parts by weight:
[0006] 70-80 parts of copper tailings;
[0007] 20-30 parts of clay;
[0008] 1 to 5 parts of limestone.
[0009] Optionally, the weight ratio of the copper tailings sand to clay is 2.48-2.85:1.
[0010] Optionally, the particle size of the copper tailings sand does not exceed 100 μm, and D50 is 1 to 50 μm.
[0011] Optionally, the particle size of the clay is less than 1 mm.
[0012] Optionally, the particle size of the limestone is less than 1 mm.
[0013] Optionally, in the cement clinker, 68%≤SiO2≤78%; 8%≤Al2O3≤14.0%; moisture content<12%; alkali content<2.5%.
[0014] In a second aspect, the present application provides a method for preparing the above-mentioned cement clinker based on copper tailings sand, comprising the following steps:
[0015] S1. Raw material crushing
[0016] Crushing copper tailings, limestone and clay to obtain raw material particles that meet the particle size requirements;
[0017] S2. Mixing and homogenization
[0018] The raw material particles prepared in S1 are mixed according to the formula ratio until they are evenly distributed to obtain a mixed raw meal;
[0019] S3. High temperature calcination
[0020] The mixed raw meal prepared in S2 is fed into a cement kiln for calcination.
[0021] Optionally, in S3, the calcination temperature is 1350-1450°C.
[0022] Optionally, in S3, the calcination time is 20 to 30 minutes.
[0023] In a third aspect, the present application provides the application of the above-mentioned cement clinker based on copper tailings sand in the field of building materials.
[0024] In summary, the present application reduces the amount of limestone and clay added by replacing a large amount of copper tailings with limestone, thereby increasing the consumption of copper tailings in cement clinker production, promoting the recycling of copper tailings, and reducing the raw material cost of cement clinker. The prepared cement clinker has excellent performance, with a free calcium oxide content of no more than 1%, and a 28d hydration compressive strength of more than 32MPa. DETAILED DESCRIPTION
[0025] The present application is further described in detail below with reference to the embodiments.
[0026] In the following examples of the present application, the main components involved, unless otherwise specified, were purchased from commercially available products.
[0027] Copper tailings sand: purchased from Tongguan Lujiang Mining Company.
[0028] Clay: particle size less than 1mm, purchased from Tongguan Lujiang Mining Company.
[0029] Limestone: particle size less than 1mm, purchased from Tongling Hongyun Calcium Industry Co., Ltd.
[0030] In the following examples of the present application, during the high-temperature calcination process, the calcination temperature is exemplarily set to 1350° C., and the calcination time is exemplarily set to 20 min. Specific embodiments
[0032] Example 1
[0033] This embodiment is used to prepare cement clinker based on copper tailings sand, and the specific method is as follows.
[0034] Suitable copper tailings sand, limestone and clay are selected and crushed to obtain raw material particles that meet the particle size requirements; the particle size of the copper tailings sand does not exceed 100 μm, and D50 is 1 to 50 μm; the particle size of the clay is less than 1 mm; and the particle size of the limestone is less than 1 mm.
[0035] The crushed raw material particles (copper tailings, clay and limestone) are mixed according to the formula ratio (7kg copper tailings, 3kg clay and 0.1kg limestone) until they are evenly distributed to obtain a mixed raw material; the mixed raw material is sent to a cement kiln for calcination, and the calcination temperature in the cement kiln is set to 1350; the calcination time is set to 20-30min.
[0036] Example 2
[0037] This embodiment is used to prepare cement clinker based on copper tailings sand, and the specific method is as follows.
[0038] Suitable copper tailings sand, limestone and clay are selected and crushed to obtain raw material particles that meet the particle size requirements; the particle size of the copper tailings sand does not exceed 100 μm, and D50 is 1 to 50 μm; the particle size of the clay is less than 1 mm; and the particle size of the limestone is less than 1 mm.
[0039] The crushed raw material particles (copper tailings, clay and limestone) are mixed according to a formula ratio (7.2 kg copper tailings, 2.8 kg clay and 0.3 kg limestone) until they are evenly distributed to obtain a mixed raw material; the mixed raw material is sent to a cement kiln for calcination, and the calcination temperature in the cement kiln is set to 1350; the calcination time is set to 20 to 30 minutes.
[0040] Example 3
[0041] This embodiment is used to prepare cement clinker based on copper tailings sand, and the specific method is as follows.
[0042] Suitable copper tailings sand, limestone and clay are selected and crushed to obtain raw material particles that meet the particle size requirements; the particle size of the copper tailings sand does not exceed 100 μm, and D50 is 1 to 50 μm; the particle size of the clay is less than 1 mm; and the particle size of the limestone is less than 1 mm.
[0043] The crushed raw material particles (copper tailings, clay and limestone) are mixed according to a formula ratio (7.4 kg copper tailings, 2.6 kg clay and 0.5 kg limestone) until they are evenly distributed to obtain a mixed raw material; the mixed raw material is sent to a cement kiln for calcination, and the calcination temperature in the cement kiln is set to 1350; the calcination time is set to 20 to 30 minutes.
[0044] Example 4
[0045] This embodiment is used to prepare cement clinker based on copper tailings sand, and the specific method is as follows.
[0046] Suitable copper tailings sand, limestone and clay are selected and crushed to obtain raw material particles that meet the particle size requirements; the particle size of the copper tailings sand does not exceed 100 μm, and D50 is 1 to 50 μm; the particle size of the clay is less than 1 mm; and the particle size of the limestone is less than 1 mm.
[0047] The crushed raw material particles (copper tailings, clay and limestone) are mixed according to a formula ratio (7.6 kg copper tailings, 2.4 kg clay and 0.5 kg limestone) until they are evenly distributed to obtain a mixed raw material; the mixed raw material is sent to a cement kiln for calcination, and the calcination temperature in the cement kiln is set to 1350; the calcination time is set to 20 to 30 minutes.
[0048] Example 5
[0049] This embodiment is used to prepare cement clinker based on copper tailings sand, and the specific method is as follows.
[0050] Suitable copper tailings sand, limestone and clay are selected and crushed to obtain raw material particles that meet the particle size requirements; the particle size of the copper tailings sand does not exceed 100 μm, and D50 is 1 to 50 μm; the particle size of the clay is less than 1 mm; and the particle size of the limestone is less than 1 mm.
[0051] The crushed raw material particles (copper tailings, clay and limestone) are mixed according to a formula ratio (7.8 kg copper tailings, 2.2 kg clay and 0.3 kg limestone) until they are evenly distributed to obtain a mixed raw material; the mixed raw material is sent to a cement kiln for calcination, and the calcination temperature in the cement kiln is set to 1350; the calcination time is set to 20 to 30 minutes.
[0052] Example 6
[0053] This embodiment is used to prepare cement clinker based on copper tailings sand, and the specific method is as follows.
[0054] Suitable copper tailings sand, limestone and clay are selected and crushed to obtain raw material particles that meet the particle size requirements; the particle size of the copper tailings sand does not exceed 100 μm, and D50 is 1 to 50 μm; the particle size of the clay is less than 1 mm; and the particle size of the limestone is less than 1 mm.
[0055] The crushed raw material particles (copper tailings, clay and limestone) are mixed according to the formula ratio (8kg copper tailings, 2kg clay and 0.1kg limestone) until they are evenly distributed to obtain a mixed raw material; the mixed raw material is sent to a cement kiln for calcination, and the calcination temperature in the cement kiln is set to 1350; the calcination time is set to 20-30min.
[0056] The free calcium oxide (f-CaO) content of the cement clinker prepared in Examples 1 to 6 was measured by the ethylene glycol method. The compressive strength (28 days of hydration) of the cement clinker was measured by GB / T 17671. The measurement results are shown in Table 1 (where c is the weight ratio of copper tailings sand to clay).
[0057] Table 1
[0058] Cement clinker c f-CaO / % Compressive strength / MPa Example 1 2.33 0.72 32.99 Example 2 2.57 0.49 35.16 Example 3 2.85 0.48 36.44 Example 4 3.17 0.55 34.81 Example 5 3.55 0.68 34.55 Example 6 4.00 0.81 33.79
[0059] It can be seen from Examples 1 to 6 and Table 1 that the free calcium oxide content of the cement clinker prepared in the present application does not exceed 1%, and the 28d hydration compressive strength can reach more than 32MPa. A large amount of copper tailings sand is added to the technical solution of the present application, thereby replacing a large amount of limestone and part of the clay, and the various properties of the prepared cement clinker meet the performance requirements.
[0060] Further analysis of Table 1 shows that the performance of the cement clinker prepared in Example 2 and Example 3 is better than that of other examples; the inventors made the following Examples 7 to 18 to further analyze the effect of the addition amount of copper tailings sand and clay on the performance of cement clinker.
[0061] Examples 7 to 13 are based on Example 2, except that only the amount of clay added is changed to obtain different weight ratios of copper tailings sand to clay; the details are as follows.
[0062] Example 7
[0063] This embodiment is used to prepare cement clinker based on copper tailings sand, and the specific method is as follows.
[0064] Suitable copper tailings sand, limestone and clay are selected and crushed to obtain raw material particles that meet the particle size requirements; the particle size of the copper tailings sand does not exceed 100 μm, and D50 is 1 to 50 μm; the particle size of the clay is less than 1 mm; and the particle size of the limestone is less than 1 mm.
[0065] The crushed raw material particles (copper tailings, clay and limestone) are mixed according to a formula ratio (7.2 kg copper tailings, 3 g clay and 0.3 kg limestone) until they are evenly distributed to obtain a mixed raw material; the mixed raw material is sent to a cement kiln for calcination, and the calcination temperature in the cement kiln is set to 1350; the calcination time is set to 20 to 30 minutes.
[0066] Example 8
[0067] This embodiment is used to prepare cement clinker based on copper tailings sand, and the specific method is as follows.
[0068] Suitable copper tailings sand, limestone and clay are selected and crushed to obtain raw material particles that meet the particle size requirements; the particle size of the copper tailings sand does not exceed 100 μm, and D50 is 1 to 50 μm; the particle size of the clay is less than 1 mm; and the particle size of the limestone is less than 1 mm.
[0069] The crushed raw material particles (copper tailings, clay and limestone) are mixed according to a formula ratio (7.2 kg copper tailings, 2.9 g clay and 0.3 kg limestone) until they are evenly distributed to obtain a mixed raw material; the mixed raw material is sent to a cement kiln for calcination, and the calcination temperature in the cement kiln is set to 1350; the calcination time is set to 20 to 30 minutes.
[0070] Example 9
[0071] This embodiment is used to prepare cement clinker based on copper tailings sand, and the specific method is as follows.
[0072] Suitable copper tailings sand, limestone and clay are selected and crushed to obtain raw material particles that meet the particle size requirements; the particle size of the copper tailings sand does not exceed 100 μm, and D50 is 1 to 50 μm; the particle size of the clay is less than 1 mm; and the particle size of the limestone is less than 1 mm.
[0073] The crushed raw material particles (copper tailings, clay and limestone) are mixed according to the formula ratio (7.2 kg copper tailings, 2.7 g clay and 0.3 kg limestone) until they are evenly distributed to obtain a mixed raw material; the mixed raw material is sent to a cement kiln for calcination, and the calcination temperature in the cement kiln is set to 1350; the calcination time is set to 20 to 30 minutes.
[0074] Example 10
[0075] This embodiment is used to prepare cement clinker based on copper tailings sand, and the specific method is as follows.
[0076] Suitable copper tailings sand, limestone and clay are selected and crushed to obtain raw material particles that meet the particle size requirements; the particle size of the copper tailings sand does not exceed 100 μm, and D50 is 1 to 50 μm; the particle size of the clay is less than 1 mm; and the particle size of the limestone is less than 1 mm.
[0077] The crushed raw material particles (copper tailings, clay and limestone) are mixed according to a formula ratio (7.2 kg copper tailings, 2.6 g clay and 0.3 kg limestone) until they are evenly distributed to obtain a mixed raw material; the mixed raw material is sent to a cement kiln for calcination, and the calcination temperature in the cement kiln is set to 1350; the calcination time is set to 20 to 30 minutes.
[0078] Embodiment 11
[0079] This embodiment is used to prepare cement clinker based on copper tailings sand, and the specific method is as follows.
[0080] Suitable copper tailings sand, limestone and clay are selected and crushed to obtain raw material particles that meet the particle size requirements; the particle size of the copper tailings sand does not exceed 100 μm, and D50 is 1 to 50 μm; the particle size of the clay is less than 1 mm; and the particle size of the limestone is less than 1 mm.
[0081] The crushed raw material particles (copper tailings, clay and limestone) are mixed according to a formula ratio (7.2 kg copper tailings, 2.5 g clay and 0.3 kg limestone) until they are evenly distributed to obtain a mixed raw material; the mixed raw material is sent to a cement kiln for calcination, and the calcination temperature in the cement kiln is set to 1350; the calcination time is set to 20 to 30 minutes.
[0082] Example 12
[0083] This embodiment is used to prepare cement clinker based on copper tailings sand, and the specific method is as follows.
[0084] Suitable copper tailings sand, limestone and clay are selected and crushed to obtain raw material particles that meet the particle size requirements; the particle size of the copper tailings sand does not exceed 100 μm, and D50 is 1 to 50 μm; the particle size of the clay is less than 1 mm; and the particle size of the limestone is less than 1 mm.
[0085] The crushed raw material particles (copper tailings, clay and limestone) are mixed according to a formula ratio (7.2 kg copper tailings, 2.4 g clay and 0.3 kg limestone) until they are evenly distributed to obtain a mixed raw material; the mixed raw material is sent to a cement kiln for calcination, and the calcination temperature in the cement kiln is set to 1350; the calcination time is set to 20 to 30 minutes.
[0086] Embodiment 13
[0087] This embodiment is used to prepare cement clinker based on copper tailings sand, and the specific method is as follows.
[0088] Suitable copper tailings sand, limestone and clay are selected and crushed to obtain raw material particles that meet the particle size requirements; the particle size of the copper tailings sand does not exceed 100 μm, and D50 is 1 to 50 μm; the particle size of the clay is less than 1 mm; and the particle size of the limestone is less than 1 mm.
[0089] The crushed raw material particles (copper tailings, clay and limestone) are mixed according to a formula ratio (7.2 kg copper tailings, 2.3 g clay and 0.3 kg limestone) until they are evenly distributed to obtain a mixed raw material; the mixed raw material is sent to a cement kiln for calcination, and the calcination temperature in the cement kiln is set to 1350; the calcination time is set to 20 to 30 minutes.
[0090] The free calcium oxide (f-CaO) content of the cement clinkers of Examples 7 to 13 was measured by the ethylene glycol method. The compressive strength (28 days of hydration) of the cement clinker was measured by GB / T 17671. The measurement results are shown in Table 2 (where c is the weight ratio of copper tailings sand to clay).
[0091] Table 2
[0092]
[0093]
[0094] By comparing Examples 7 to 13 with Example 2 and Table 2, it can be seen that the weight ratio of copper tailings sand to clay in the technical solution of the present application is between 2.48 and 2.77:1, the free calcium oxide content of the prepared cement clinker does not exceed 0.5%, and the 28d hydration compressive strength can reach more than 35MPa.
[0095] Examples 14 to 18 are based on Example 3, except that only the amount of clay added is changed to obtain different weight ratios of copper tailings sand to clay; the details are as follows.
[0096] Embodiment 14
[0097] This embodiment is used to prepare cement clinker based on copper tailings sand, and the specific method is as follows.
[0098] Suitable copper tailings sand, limestone and clay are selected and crushed to obtain raw material particles that meet the particle size requirements; the particle size of the copper tailings sand does not exceed 100 μm, and D50 is 1 to 50 μm; the particle size of the clay is less than 1 mm; and the particle size of the limestone is less than 1 mm.
[0099] The crushed raw material particles (copper tailings, clay and limestone) are mixed according to a formula ratio (7.4 kg copper tailings, 3 kg clay and 0.5 kg limestone) until they are evenly distributed to obtain a mixed raw material; the mixed raw material is sent to a cement kiln for calcination, and the calcination temperature in the cement kiln is set to 1350; the calcination time is set to 20 to 30 minutes.
[0100] Embodiment 15
[0101] This embodiment is used to prepare cement clinker based on copper tailings sand, and the specific method is as follows.
[0102] Suitable copper tailings sand, limestone and clay are selected and crushed to obtain raw material particles that meet the particle size requirements; the particle size of the copper tailings sand does not exceed 100 μm, and D50 is 1 to 50 μm; the particle size of the clay is less than 1 mm; and the particle size of the limestone is less than 1 mm.
[0103] The crushed raw material particles (copper tailings, clay and limestone) are mixed according to the formula ratio (7.4 kg copper tailings, 2.9 kg clay and 0.5 kg limestone) until they are evenly distributed to obtain a mixed raw material; the mixed raw material is sent to a cement kiln for calcination, and the calcination temperature in the cement kiln is set to 1350; the calcination time is set to 20 to 30 minutes.
[0104] Example 16
[0105] This embodiment is used to prepare cement clinker based on copper tailings sand, and the specific method is as follows.
[0106] Suitable copper tailings sand, limestone and clay are selected and crushed to obtain raw material particles that meet the particle size requirements; the particle size of the copper tailings sand does not exceed 100 μm, and D50 is 1 to 50 μm; the particle size of the clay is less than 1 mm; and the particle size of the limestone is less than 1 mm.
[0107] The crushed raw material particles (copper tailings, clay and limestone) are mixed according to a formula ratio (7.4 kg copper tailings, 2.8 kg clay and 0.5 kg limestone) until they are evenly distributed to obtain a mixed raw material; the mixed raw material is sent to a cement kiln for calcination, and the calcination temperature in the cement kiln is set to 1350; the calcination time is set to 20 to 30 minutes.
[0108] Embodiment 17
[0109] This embodiment is used to prepare cement clinker based on copper tailings sand, and the specific method is as follows.
[0110] Suitable copper tailings sand, limestone and clay are selected and crushed to obtain raw material particles that meet the particle size requirements; the particle size of the copper tailings sand does not exceed 100 μm, and D50 is 1 to 50 μm; the particle size of the clay is less than 1 mm; and the particle size of the limestone is less than 1 mm.
[0111] The crushed raw material particles (copper tailings, clay and limestone) are mixed according to a formula ratio (7.4 kg copper tailings, 2.7 kg clay and 0.5 kg limestone) until they are evenly distributed to obtain a mixed raw material; the mixed raw material is sent to a cement kiln for calcination, and the calcination temperature in the cement kiln is set to 1350; the calcination time is set to 20 to 30 minutes.
[0112] Embodiment 18
[0113] This embodiment is used to prepare cement clinker based on copper tailings sand, and the specific method is as follows.
[0114] Suitable copper tailings sand, limestone and clay are selected and crushed to obtain raw material particles that meet the particle size requirements; the particle size of the copper tailings sand does not exceed 100 μm, and D50 is 1 to 50 μm; the particle size of the clay is less than 1 mm; and the particle size of the limestone is less than 1 mm.
[0115] The crushed raw material particles (copper tailings, clay and limestone) are mixed according to a formula ratio (7.4 kg copper tailings, 2.5 kg clay and 0.5 kg limestone) until they are evenly distributed to obtain a mixed raw material; the mixed raw material is sent to a cement kiln for calcination, and the calcination temperature in the cement kiln is set to 1350; the calcination time is set to 20 to 30 minutes.
[0116] The free calcium oxide (f-CaO) content of the cement clinkers of Examples 14 to 18 was measured by the ethylene glycol method. The compressive strength (28 days of hydration) of the cement clinker was measured by GB / T 17671. The measurement results are shown in Table 3 (where c is the weight ratio of copper tailings sand to clay).
[0117] Table 3
[0118]
[0119]
[0120] By comparing Examples 14 to 18 with Example 3 and Table 3, it can be seen that the weight ratio of copper tailings sand to clay in the technical solution of the present application is between 2.55 and 2.85:1, the free calcium oxide content of the prepared cement clinker does not exceed 0.5%, and the 28d hydration compressive strength can reach more than 35MPa.
[0121] By comparing Examples 7 to 18 with Examples 2 to 3 and Tables 2 to 3, it can be seen that the weight ratio of copper tailings sand to clay in the technical solution of the present application is between 2.48 and 2.85:1, the free calcium oxide content of the prepared cement clinker does not exceed 0.5%, and the 28d hydration compressive strength can reach more than 35MPa.
[0122] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.
Claims
1. A cement clinker based on copper tailings sand, characterized in that: The cement clinker is prepared from the following components in parts by weight: 70-80 parts of copper tailings; 20-30 parts of clay; 1 to 5 parts of limestone.
2. The cement clinker based on copper tailings sand according to claim 1, characterized in that: The weight ratio of the copper tailings sand to clay is 2.48-2.85:
1.
3. The cement clinker based on copper tailings sand according to claim 1, characterized in that: The particle size of the copper tailings sand does not exceed 100 μm, and D50 is 1 to 50 μm.
4. The cement clinker based on copper tailings sand according to claim 1, characterized in that: The particle size of the clay is less than 1 mm.
5. The cement clinker based on copper tailings sand according to claim 1, characterized in that: The particle size of the limestone is less than 1 mm.
6. The cement clinker based on copper tailings sand according to claim 1, characterized in that: In the cement clinker, 68%≤SiO2≤78%; 8%≤Al2O3≤14.0%; moisture content<12%; alkali content<2.5%.
7. A method for preparing cement clinker based on copper tailings sand according to claim 1, characterized in that: The following steps are involved: S1. Raw material crushing Crushing copper tailings, limestone and clay to obtain raw material particles that meet the particle size requirements; S2. Mixing and homogenization The raw material particles prepared in S1 are mixed according to the formula ratio until they are evenly distributed to obtain a mixed raw meal; S3. High temperature calcination The mixed raw meal prepared in S2 is fed into a cement kiln for calcination.
8. The cement clinker based on copper tailings sand according to claim 1, characterized in that: In the above-mentioned S3, the calcination temperature is 1350-1450°C.
9. The cement clinker based on copper tailings sand according to claim 1, characterized in that: In the step S3, the calcination time is 20 to 30 minutes.
10. Use of the cement clinker based on copper tailings sand according to claim 1 in the field of building materials.
Citation Information
Cited By
Copper tailing regenerated cement admixture and preparation method thereof
CN120987627A